Small Scale Dairy Farms Integration in Competitive Value Chains in Khartoum- Sudan - Fawi, Nahid, M. T.; Eltayeb, B. E. A. (Journal of Veterinary Medicine and Animal Production, 2021)
This study aimed to analyze the dairy value chain to identify production potential, key sector constraints, opportunities and appropriate intervention, in order to identify policy and market based solutions that address the dairy industry. Farm owners in Mahlab (2) - Kuku in Khartoum North were the population of the sample; study was performed during 2013- 2014. A stratified random sampling procedure was adopted to select 75 producers as the sample of this study. The study was based mainly on primary data collected from the selected farms using a structured cross sectional questionnaire. Collected data was analyzed, using the statistical package for social sciences SPSS (Version 11.5), to obtain the frequency distributions. The study recommended that enforcement of developed standards in the dairy industry should be performed by policy makers that involves all players in this sector; support of managemental practices to develop human and technical capacity to develop local milk standards that could meet regional and international standards; strengthen partnership between private and public sector with a view to acquiring relevant technologies and capacity building and integration of small scale dairy farms in the dairy value chain through opening new marketing opportunities.